Integrasi Pembelajaran Berbasis Proyek Video untuk Mengembangkan Berpikir Kreatif dalam Pendidikan Diploma Teknologi Informasi - Ariel Yonatan Alin; Muhammad Hassan Massaty; Aditya Wahyu Ramadhan (MASALIQ, 2026)
Although previous studies have examined the use of video-based project learning, research that specifically investigates its impact on the development of creative thinking skills in Information Technology education remains limited. This study aims to analyze the influence of integrating Video Project-Based Learning (VPBL) on the creative thinking abilities of students in a Diploma Program in Information Technology. Employing a mixed-methods design with a quasi-experimental approach, the study involved 20 students and collected data through the Torrance’s Test of Creative Thinking, classroom observations, and reflective journals. The data were analyzed using thematic analysis and descriptive statistics to map changes in students’ creative thinking skills. The findings indicate a significant increase in creative thinking abilities, with an average score rise of 0.79 points across the four measured dimensions of creativity. These results enrich theories of project-based learning and creativity, while providing deeper insights into the application of multimedia in vocational education. The study concludes that the use of video in learning can enhance students’ creative abilities and recommends that educational institutions integrate this model into their curricula. The implications include theoretical contributions to the development of the project-based learning literature and practical recommendations for designing more innovative curricula that are relevant to the needs of the digital industry, as well as opening opportunities for further research on the integration of multimedia technology in various fields of learning.